Jaringan Seksual dan Perilaku Berisiko Pengguna Napza Suntik: Episode Lain Penyebaran HIV di Indonesia - Ignatius Praptoraharjo, Wayne W. Wiebel, Octavery Kamil, Alfred Pach III (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background: Although a relative late comer to the epidemic, HIV has struck Indonesia hard. Surveillance at the Ministry of Health’s drug dependence hospital showed an escalation from 0% injecting drug users (IDUs) infected in 1997 to almost 50% infected by 2001. As more injectors become infected, the potential for sexual transmission of HIV by IDUs increases. Yet, little was known about IDU sexual networks, sexual partnering patterns, the nature of sexual relationships and sex risk practices.Methods: IDUs are concentrated in major metropolitan areas across the Indonesian archipelago. The country’s five largest cities (Jakarta, Surabaya, Medan, Bandung and Denpasar) were selected for inclusion here because they include various concentrations of IDU, potentially different, patterns of sexual networking and risk. Participants were recruited with the assistance of local, non-governmental organizations working on HIV/AIDS interventions targeting IDUs. A purposive sampling design sought to include subjects representing the range in known IDU characteristics at each locale. Selection criteria included active injectors who were sexually active and 18 years of age or older. Following informed consent, 52 willing respondents were interviewed using a semi- structured and open-ended interview guide. Interviews were divided into narrative passages and coded as to topical content upon entry in EZText qualitative database software.Results: Indonesian IDUs were found to commonly have regular, casual and commercial sex partners. Almost 90% were involved in a serious relationship with a spouse or girl/boy friend. Serious relationships included emotional ties and mutual expectations and obligations. The most common expectation was faithfulness, yet 75% of those with a regular sex partner had concurrent relations with casual and/or commercial partners. Most male IDUs actively pursued casual and commercial relations. Male IDUs also reported sex with transgenders and other males. Condoms were rarely used irrespective of partner category.Conclusion: The frequency of unprotected relations with a variety in types of partners suggests a high potential for the bridging of HIV to non-IDU populations in Indonesia. Information learned about types of partnerships and relations suggest different strategies will be needed for different types of partners if a generalized epidemic is to be averted.Keywords: injecting drug users, HIV, sexual partner, risk network, intervention